Prognosis of variceal and non‐variceal upper gastrointestinal bleeding in already hospitalised patients: Results from a French prospective cohort. Issue 6 (8th June 2021) - EL Hajj, Weam; Quentin, Vincent; Boudoux D'Hautefeuille, Gaelle; Vandamme, Helene; Berger, Chantal; Moussaoui, Mohammed Redha; Berete, Aliou; Louvel, Dominique; Bertolino, Jean Guy; Cuillerier, Emmanuel; Thiebault, Quentin; Arondel, Yves; et al.
Abstract: Objectives: Patients who develop upper gastrointestinal bleeding (UGIB) while in hospital appear to have a poor prognosis. Our study aims at analysing the difference in outcome between in‐patients (IPs) and out‐patients presenting with variceal and non‐variceal UGIB. Methods: We conducted a multicentre prospective study by collecting data about variceal and non‐variceal UGIB cases through 46 hospitals in France between November 2017 and October 2018. We then compared baseline demographic features, endoscopic findings and outcome between patients who developed variceal and non‐variceal UGIB on admission (OPs) and those at least 24 h after hospitalisation (IPs). Our primary end‐point was mortality and re‐bleeding rates at 6 weeks of bleeding onset. Results: A total of 2498 UGIB cases were identified, of whom 634 (25.4%) occurred in IPs. IPs were older than OPs (72.5 vs. 67.2 years old, p  < 0.001) and had a higher rate of comorbidities (38.9% vs. 26.6%, p  < 0.0001). Their bleeding was more severe with a Rockall score of >5 present in 40.9% (vs. 30.3% in OPs, p  < 0.0001). The 6‐week mortality rate was significantly higher in IPs when compared to OPs (21.7% vs. 8%, p  < 0.0001). Prothrombin time <50% and rebleeding were the only independent predictors of mortality ( p  = 0.001 and 0.003, respectively). Six‐week rebleeding occurred more frequently among IPs (18.6% vs. 14.4%, p  = 0.015) and predictors included female sex, active bleeding upon endoscopy and a Blatchford score >11 ( p  = 0.017, 0.011 and 0.008, respectively). Conclusion: IPs who develop variceal and non‐variceal UGIB are more likely to be elderly with more comorbidities. They have a higher rate of mortality and rebleeding. Independent predictors of mortality were underlying coagulopathy and bleeding recurrence. An optimal bleeding management and efficient rebleeding prevention may improve outcome in these patients. Key Point: Summarize the established knowledge on this subject Upper gastrointestinal bleeding (UGIB) in already hospitalised patients (IPs) appears to have a worse prognosis when compared to UGIB in out‐patients (OPs). Few studies have addressed this issue, most of which are retrospective. They found a poor short‐term outcome in IPs without being able to identify modifiable risk factors that could affect the prognosis. Significant and/or new findings of this study? We demonstrated in this prospective and multicentre study a greater 6‐week mortality and rebleeding rates in IPs versus OPs. IPs were older and had a higher rate of comorbidities. Prothrombin time <50% and rebleeding were independently associated with a higher mortality rate in IPs. An appropriate bleeding management and an optimal rebleeding prevention plan might improve the outcome of UGIB in already hospitalised patients.